2011
DOI: 10.1007/s10633-011-9294-x
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinogram findings in unilateral optic neuritis

Abstract: To report the electrophysiological findings in patients with unilateral optic neuritis (ON), with particular reference to the electroretinogram (ERG). A retrospective analysis of full-field ERG, pattern ERG (PERG) and pattern visual evoked potential findings from 46 patients with clinical and electrophysiological findings in keeping with unilateral ON. ISCEV standard ERGs did not significantly differ between the optic neuritis and fellow eyes, nor between patients with and without MS. Differences were present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
14
1
1
Order By: Relevance
“…Previous work examining the ERG in MS patients has produced apparently contradictory findings, with some authors reporting normal ERG results [28][29][30] and others a range of abnormalities. [11][12][13][31][32][33][34] Significantly, those studies that reported normal ERG findings in MS patients analyzed only response amplitudes, with no peak time values presented.…”
Section: Discussionmentioning
confidence: 96%
“…Previous work examining the ERG in MS patients has produced apparently contradictory findings, with some authors reporting normal ERG results [28][29][30] and others a range of abnormalities. [11][12][13][31][32][33][34] Significantly, those studies that reported normal ERG findings in MS patients analyzed only response amplitudes, with no peak time values presented.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, a-and b-wave amplitudes were not significantly different in the MS eyes than in the control eyes, as reported recently in standard clinical testing. 48 As noted above, distal retinal function, documented by ERG a-and b-waves, can be affected in the acute phase of ON. 40 However, in the present study, in which recordings were made after an acute episode, there was only a hint of lower a-and b-wave amplitudes in ONϽ6 eyes, especially when compared to the eyes without a history of ON.…”
Section: Outer Retinal Integrity In Ms Patientsmentioning
confidence: 92%
“…96 The PERG is a surrogate test of macular function, and can, therefore, be used to differentiate macular from optic nerve causes of central vision loss. The two main components of the PERG are N95 and P50, 96,101,102 and the N95 component and N95:P50 ratio were found to be useful in optic neuritis. [101][102][103][104] The optic nerve head component responses of multifocal ERG may also emerge as a useful tool in the assessment of optic neuritis.…”
Section: Research Protocolmentioning
confidence: 96%